Introduction: Citizenship Surveillance of La Gente (The People)—Theory, Practice, and Cultural Citizen Voices - Ballasch, Melissa M. (Social justice, 2008)
Part of a special issue on Latino citizenship and social justice. A commentary on five articles by various writers that appeared in this issue on pp. 7–108. In their articles, the writers drew heavily on narratives from ethnographic research, case studies, or personal testimonies, to present the perspective of la gente, the Latino people who live within U.S. society, concerning citizenship as a “lived” experience. The commentator observes that the articles challenge normalized ideas of citizenship and lists the troubling ways in which exclusion from citizenship is normalized and operationalized in schools and society; she agrees that their call for citizenship inclusion of Latinos is critical.